Enhancing Agile Software Development: A Comprehensive Framework for Metrics-Driven Performance Evaluation - Raju Ramakrishna Gondkar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the realm of Agile software development, the quest for efficient performance evaluation methodologies remains paramount. Grounded in empirical research and industry best practices, our framework offers a systematic approach to gauge the efficacy and productivity of Agile teams through a meticulous selection of metrics. Emphasizing the significance of quantitative analysis, our framework advocates for a balanced blend of traditional and Agile-specific metrics, encompassing aspects such as velocity, cycle time, and customer satisfaction. By leveraging this comprehensive array of metrics, organizations can gain nuanced insights into team dynamics, project progress, and overall performance, thereby fostering a culture of continuous improvement and informed decision-making. Furthermore, our framework incorporates mechanisms for adaptability, acknowledging the dynamic nature of Agile environments and the need for iterative refinement. Through a rigorous validation process involving real-world case studies and industry feedback, we demonstrate the practical applicability and efficacy of our framework across diverse Agile contexts. Ultimately, our research contributes to the advancement of Agile software development practices by providing a robust foundation for objective performance evaluation, facilitating the pursuit of excellence and agility in software delivery.